“Dolor, niños y arte”: Oncología y trasplantes pediátricos - Rico, Laura (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
The artistic creation is a vehicle for the expression, the communication and the personal development. As such it can be used to help the patient and being bridge between the internal and external world. In pediatrics it is especially useful because of the children’s difficulties to verbalize and to recognize emotions when they go into the, until then, unknown world of the illness. Likewise it is an effective assistant in the confrontation with the pain. Based on the investigation about artherapy developed in big hospitals of Spain (La Paz; Madrid): pediatric oncology and transplants services floors.
Keywords: Artherapy; Psychology; Health